2005
DOI: 10.1002/hbm.20187
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on cortical thickness and the influence of scaling

Abstract: Using magnetic resonance imaging and well-validated computational cortical pattern matching methods in a large and well-matched sample of healthy subjects (n = 60), we analyzed the regional specificity of gender-related cortical thickness differences across the lateral and medial cortices at submillimeter resolution. To establish the influences of brain size correction on gender effects, comparisons were performed with and without applying affine transformations to scale each image volume to a template. We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
191
5
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(228 citation statements)
references
References 70 publications
29
191
5
3
Order By: Relevance
“…Previous studies investigating sex differences in the human brain have also detected increased volume or cortical thickness in the GM comprising the superior frontal and more medial sections of the frontal cortex in women compared to men (Goldstein et al, 2001;Good et al, 2001;Lombardo et al, 2012;Luders et al, 2006Luders et al, , 2009a. It should be noted that in this study we did not obtain information regarding the menstrual cycle in the girls, and therefore we cannot exclude subtle cycle-related effects on GM volumes.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies investigating sex differences in the human brain have also detected increased volume or cortical thickness in the GM comprising the superior frontal and more medial sections of the frontal cortex in women compared to men (Goldstein et al, 2001;Good et al, 2001;Lombardo et al, 2012;Luders et al, 2006Luders et al, , 2009a. It should be noted that in this study we did not obtain information regarding the menstrual cycle in the girls, and therefore we cannot exclude subtle cycle-related effects on GM volumes.…”
Section: Discussionmentioning
confidence: 63%
“…Rate of change in surface complexity S estimated by finite differencing at visit 2 in all the subjects who provided MRI data for a total of 3 visits. Other studies that have investigated the cortical surface area have reported that male brains have greater cortical surface area than female brains when measured in their native space [22][23][24], but when area measurements were normalized by volume, females actually had more surface area than males [23], though not significantly. However, an investigation of cortical surface area did show highly significant sex differences after image scaling [24].…”
Section: Discussionmentioning
confidence: 88%
“…Other studies that have investigated the cortical surface area have reported that male brains have greater cortical surface area than female brains when measured in their native space [22][23][24], but when area measurements were normalized by volume, females actually had more surface area than males [23], though not significantly. However, an investigation of cortical surface area did show highly significant sex differences after image scaling [24]. Two other studies also provided evidence for direct sex effects of cortical complexity in which the female brain revealed greater cortical complexity compared to males [2,24].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations